PERAN AKTOR DAN RELASI KUASA DALAM FORMULASI KEBIJAKAN JAKARTA SMART CITY - Annisa Suryamadani (2021)
This study aims to discuss the political dynamics in the formulation of policies and programs for the development of Jakarta Smart City (JSC) using public policy theory, policy network theory, and institutional theory. The method used is descriptive qualitative. The final result of this study shows that institutions would need to involve various stakeholders to determine common interests. The involvement of various actors in the formulation of the JSC policy consists of the DKI Jakarta Provincial Government, TGUPP, Prof. Eko Prasojo, Ministry of Home Affairs, Legal Bureau, ORB Bureau, BPKD, BAPPEDA, inspectorate, DPRD, DISKOMINFOTIK, private sector, academics, NGOs, and mass media where the Provincial Government of DKI Jakarta as a local government institution has a central role as a facilitator, coordinator, entrepreneur, and stimulator based on its authority and capability to manage and implement the JSC development program which is actualized in the form of a local government work plan that is outlined in the form of regional income, expenditure and financing. In addition, in the development of the JSC, it was found that community participation is still in a one-way form because the public is only able to report through the complaint channel and convey their aspirations in the e-musrenbang. Its implication has not been able to intervene in determining policy directions. In addition, the development of JSC and ongoing cooperation are still in the scope of the development of applications, CCTV, and control rooms.